Kelembagaan Komunitas Rehabilitasi Lingkungan (RHBS) Pandeglang dalam Gerakan Pelestarian Lingkungan di Desa Teluk Pandeglang - Eneng Nurul Prihatini; Nurul Hayat; Yustika Irfani Lindawati (PADARINGAN (Jurnal Pendidikan Sosiologi Antropologi), 2024)
This article aims to describe the environmental rehabilitation community movement (RHBS) as an environmental conservation organization in Teluk Pandeglang Village. Teluk Village is located in Labuan District, Pandeglang Regency, Banten, with part of its area located on the sea coast. Behind the village's appeal as a tourist destination, there is the problem of piles of rubbish which can reach a volume of 1 ton per day. This problem has an impact on public health and hampers the socio-economic activities of the Teluk Village community. The Pandeglang Environmental Rehabilitation Community (RHBS) is a form of youth restlessness in Teluk Village. The emergence of the RHBS community is analyzed using the concept of a new social movement (NSM) according to Hubermast, where the movement carried out aims to restore the village's environmental conditions to a waste-free condition by minimizing the impact of waste on life. public. As an environmental conservation movement organization that plays a role as (1) Balancing; Direct action through the Garbage Collection Movement (GPS) and Advocacy (indirect action) through promoting waste processing programs and conveying community complaints, (2) Community Empowerment through Rehabilitation Waste Banks, waste sorting houses and Environmental Education Socialization, (3) Intermediary Institutions in collaboration with the World Clean Up Day (WCD) Rehabilitation Foundation and the Teluk Village government through the "follow the river" movement. Based on analysis using Anthony Oberschall's resource mobilization theory, it was found that the RHBS Community has material, moral, organizational, cultural and human resources which are mobilized through various programs to create a sustainable movement. As an organization/institution, RHBS becomes a tool of social control in environmental conservation through the movements it carries out.